Experimental and theoretical study on the behaviour of a pickling solution: The role of ferrous ions. (10th January 2020) - Yang, Fangming; Wu, Yan; Fang, Xiting; Ma, Lijuan
Abstract: The existence of ferrous ions plays an important role in the performance of pickling liquor as well as the recovery of hydrochloric acid from waste pickling liquor. The promotion mechanism and the interaction between ferrous ions and hydrogen chloride molecules have remained largely unsolved. In this research, the fundamental aspects of a simulated hydrochloric acid pickling solution with different concentrations of ferrous ions were experimentally and theoretically studied. The experimental results showed that the existence of ferrous ions in the pickling liquor effectively inhibited the volatilisation of hydrogen chloride from solution and that the inhibition of volatilisation enhanced with an increase in concentration of ferrous ions. To understand the interaction between ferrous ions and hydrogen chloride molecules, the structure and thermodynamic properties of possible hydration structures were obtained by using molecular simulation. The results showed that a new type of cluster, hydrogen chloride-ferrous ion-water, was formed in the presence of ferrous ions, which made the hydrogen chloride molecules in the pickling liquor more stable compared to the same condition without ferrous ions. The existence of ferrous ions in pickling liquor benefits the pickling process from an economic and environmental aspect. Graphical abstract: Image 1054 Highlights: Temperature and acid concentration affected the volatilisation of pickling liquor. The presence of ferrous ions inhibited the volatilisation of pickling liquor. [Fe(H2 O)n ] 2+ (HCl) was formed in hydrochloric acid pickling solution. [Fe(H2 O)n ] 2+ (HCl) clusters were more stable compared to (HCl)n (H2 O)10 clusters.